Multicomponent Fe-based composites derived from the oxidation and reduction of Prussian blue towards efficient electromagnetic wave absorption. Issue 16 (12th April 2021) - Liu, Wei; Duan, Pengtao; Xiong, Hanwu; Su, Hailin; Zhang, Xuebin; Wang, Jinzhi; Yang, Fuyao; Zou, Zhongqiu
Abstract : The flexible design of composition for Fe-based composites via novel oxidation–polymerization–reduction routes enables improved microwave absorption performance at low thickness. Abstract : Broadband microwave absorption at low thickness still remains a challenge for most microwave absorbing materials derived from metal–organic frameworks. Herein, a three-step route, including the oxidation of Prussian blue microcubes, polymerization of phenolic resin on Fe2 O3 microcubes and controllable carbothermal reduction of Fe2 O3 @resin, has been developed to achieve simultaneous enhancement of complex permittivity and permeability, in order to promote reflection loss performance at low thickness. It has been proved that different carbothermal reduction environments generated by different resin contents would have a direct effect on the composition and microstructures of the reduced products. In detail, irregular particles of reduced products tend to grow up and connect with each other with increasing resin content. With low resin content, the reduced products (CR-0.2 and CR-0.4) consist of Fe3 O4, FeO and Fe. With high resin content, the reduced products (CR-0.6 and CR-0.8) are composed of Fe3 O4, Fe, Fe3 C and partially graphitic carbon. A higher reduction degree endows CR-0.6 and CR-0.8 with stronger attenuation ability, including conduction loss provided by metallic Fe and graphitic carbon frameworks, enhanced polarization loss generated among multiple interfaces and magnetic loss produced by Fe and Fe3 O4 . Owing to the good balance between electromagnetic attenuation and impedance matching, a broad effective absorption bandwidth of 5.44 GHz can be reached at only 1.5 mm for CR-0.6. Our findings may pave a new way for realizing broadband microwave absorption at low thickness and offer novel insights for designing the composition and structure of MOF-derived materials.